Avaliação das dimensões da qualidade de vida de pessoas com leishmaniose - Silva Júnior, Sérgio Vital da (2020)
Introduction: Leishmaniasis is a tropical disease of complex epidemiology and ecology, currently constituting an important public health problem. Cutaneous leishmaniasis presents as an ulcer that can lead to scarring, deformation and stigmatization. Visceral leishmaniasis is the most severe, systemic form, and is usually fatal if left untreated. Such clinical situations may contribute to a consequent decrease in the quality of life of individuals affected by the disease. Thus, the present investigation aimed to assess the health-related quality of life of people with visceral leishmaniasis and cutaneous leishmaniasis according to sociodemographic, epidemiological and clinical aspects. Method: Exploratory and descriptive cross-sectional study with a quantitative approach, developed at the Infectious and Parasitic Diseases Unit of a reference hospital for the treatment of this condition in Paraíba, Brazil. The sample was of the probabilistic type, being considered as inclusion criteria: people over 18 years old, of both sexes, with a medical diagnosis of leishmaniasis (visceral or cutaneous) being treated at the referred health service. Exclusion criteria were: patients who were using psychotropic drugs, with physical or cognitive disabilities to answer the questionnaires used in the investigation. Initially, a questionnaire was applied in search of information about patient identification, housing conditions, clinical aspects and tests performed, in addition to the questionnaire for measuring quality of life (Medical Outcomes Survey Short-Form 36). For data collection, the participant's consent was requested through the Free and Informed Consent Form. The data were tabulated in a Microsoft Office Excel 2010 spreadsheet and later transferred to the Statistical Package for the Social Sciences software version 20. For data analysis, descriptive measures (frequency, mean and standard deviation) and non-parametric statistical tests were used Mann-Whitney and Kruskal-Wallis. This study received approval from the Research Ethics Committee, with CAAE number: 11309619.9.0000.5183. Results: 45 of whom participated in the investigation, 22 of whom were affected by american cutaneous leishmaniasis and 23 by visceral leishmaniasis. With regard to american cutaneous leishmaniasis, a negative impact on quality of life was observed in all domains, with lower SF 36 scores on physical function, emotional role and vitality. Regarding visceral leishmaniasis, it was evidenced that there is a negative impact on all scores in the SF 36 domains, especially in the emotional role, physical function and social function domains. Conclusion: The present study made it possible to understand the epidemiological characteristics of leishmaniasis in the state of Paraíba, in addition to evaluating the health-related quality of life of people affected by this infection according to sociodemographic, epidemiological and clinical aspects. That said, health professionals and managers will be able to use this information to develop immediate actions that aim to mitigate the impact of the infection on the lives of human beings, with emphasis on the affected dimensions. aspects